Hospital admissions among people who inject opioids following syringe services program implementation - K. J. Bornstein; A. E. Coye; J. E. St. Onge; H. Li; A. Muller; T. S. Bartholomew; H. E. Tookes (Harm Reduction Journal, 2020)
Abstract Background Syringe services programs (SSPs) are an evidence-based harm reduction strategy that reduces dangerous sequelae of injection drug use among people who inject drugs (PWID) such as overdose. SSP services include safer injection education and community-based naloxone distribution programs. This study evaluates differences in overdose-associated hospital admissions following the implementation of the first legal SSP in Florida, based in Miami-Dade County. Methods We performed a retrospective analysis of hospitalizations for injection drug-related sequelae at a county hospital before and after the implementation of the SSP. An algorithm utilizing ICD-10 codes for opioid use and sequelae was used to identify people who inject opioids (PWIO). Florida Department of Law Enforcement Medical Examiners Commission Report data was used to analyze concurrent overdose death trends in Florida counties. Results Over the 25-month study period, 302 PWIO admissions were identified: 146 in the pre-index period vs. 156 in the post-index period. A total of 26 admissions with PWIO overdose were found: 20 pre-index and 6 post-index (p = 0.0034). Conclusions Declining overdose-associated admissions among PWIO suggests early impacts following SSP implementation. These results indicate a potential early benefit of SSP that should be further explored for its effects on future hospital admission and mortality.